2020
DOI: 10.1155/2020/2863624
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Technique and Procedure of Stromal Vascular Fraction Therapy: From Liposuction to Cell Administration

Abstract: Background. Stromal vascular fraction (SVF) therapy has been performed over the past six years to treat 421 patients by our group in five clinical centers. Autologous SVF, which is a substance containing stem cells, was isolated from lipoaspirate, mixed with platelet-rich plasma (PRP), and administered to patients with degenerative diseases, autoimmune diseases, trauma, aging, and other diseases with unknown etiology. This study aimed to determine the safety of SVF and PRP th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 50 publications
3
21
0
Order By: Relevance
“…PRP has also been reported to be beneficial for ischemic stroke, osteoarthritis, and chronic ulcers. There have been no previous reports regarding the adverse event of PRP use in those cases or its combination with stromal vascular fraction (11,12,30,31,32,33). Our study showed that the intravenous administration of aaPRP in patients with various pathological conditions did not cause any adverse event.…”
Section: Discussionmentioning
confidence: 41%
“…PRP has also been reported to be beneficial for ischemic stroke, osteoarthritis, and chronic ulcers. There have been no previous reports regarding the adverse event of PRP use in those cases or its combination with stromal vascular fraction (11,12,30,31,32,33). Our study showed that the intravenous administration of aaPRP in patients with various pathological conditions did not cause any adverse event.…”
Section: Discussionmentioning
confidence: 41%
“…Activated autologous platelet-rich plasma (aaPRP) is a prospective therapy to be performed in COVID-19 patients to combat such systemic inflammation. Apart from its accessibility, it also possesses anti-inflammatory properties through cytokines such as interleukin-1 receptor antagonist (IL-1RA) and a known safety profile [11][12][13][14]. Similarly, anakinra, a recombinant IL1-RA, showed promising results in a cohort consisting of patients with severe forms COVID-19 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Besides being minimally invasive to extract, ADSCs are abundant in source because fat tissue can be found almost everywhere in the body. Another rationale for utilizing ADSCs as cellular therapy is their multipotency and autologous usage, which allows to avoid immunological rejection and tumorigenesis (15)(16)(17).…”
Section: Contextmentioning
confidence: 99%